2008
DOI: 10.1128/aem.00315-08
|View full text |Cite
|
Sign up to set email alerts
|

RNA Arbitrarily Primed PCR and Fourier Transform Infrared Spectroscopy Reveal Plasticity in the Acid Tolerance Response ofStreptococcus macedonicus

Abstract: We have previously reported that an acid tolerance response (ATR) can be induced in Streptococcus macedonicus cells at mid-log phase after autoacidification, transient exposure to acidic pH, or acid habituation, as well as at stationary phase. Here, we compared the transcriptional profiles of these epigenetic phenotypes, by RNA arbitrarily primed PCR (RAP-PCR), and their whole-cell chemical compositions, by Fourier transform infrared spectroscopy (FT-IR). RAP-PCR fingerprints revealed significant differences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 45 publications
(81 reference statements)
2
5
0
2
Order By: Relevance
“…Differences observed in all spectral regions were more discernible after second derivative transformation (Figure 3) as expected according to previous studies [28,29]. …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Differences observed in all spectral regions were more discernible after second derivative transformation (Figure 3) as expected according to previous studies [28,29]. …”
Section: Resultssupporting
confidence: 90%
“…After 2 h of incubation, cells were collected by centrifugation, washed twice with PBS (pH 7.2) and resuspended in 30 μL of sterile double-distilled water. FT-IR sample preparation and measurements were performed according to the methodology described before [28]. In brief, 10 μL of the resulting suspension were spotted at the center of an IR transparent ZnSe optical disc.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the FTIR--ATR spectrum of L. casei 01 before encapsulation was comparable to the spectra reported for other lactic acid bacteria, identified by the FTIR fingerprint method (39,40). As in previous studies, in which emulsion and spray drying were used for microencapsulation, the spectra of non-encapsulated and L. casei 01 released from the SPI-alginate microparticles were almost identical, with an additional band at 1127 cm -1 in the spectrum of released cells relevant for lactic acid (14,16).…”
Section: Physicochemical Properties Of L Casei 01 Encapsulated In Spsupporting
confidence: 75%
“…The authors also observed increased Raman intensity for lipids and some proteins but not for nucleic acids as a function of nanoparticle concentration indicating that nanoparticleinduced injury is likely caused by a different mechanism than antibiotic treatment in which protein and nucleic acid synthesis are inhibited. In other studies, FT-IR was used to study heat-induced lethal and sublethal injuries in Lactococcus lactis (Kilimann et al 2006), osmotic and thermally induced injuries of E. coli (Mille et al 2002), UV radiationinduced injury of Staphylococcus aureus (Krishnamurthy et al 2010), lethal injury in E. coli caused by dehydration (Beney et al 2004), radical-induced damage of Micrococcus luteus (Lorin-Latxague and Melin 2005), acid tolerance response of Streptococcus macedonicus (Papadimitriou et al 2008), and toxicity response of yeast (Corte et al 2010). Recently, the membrane phase behavior of E. coli during desiccation and rehydration was also studied by FT-IR (Scherber et al 2009).…”
Section: Studies Of Bacterial Injury and Inactivation By Vibrationalmentioning
confidence: 99%